SISTEM INFROMASI RETRIBUSI PASAR CITRA NIAGA SAMARINDA BERBASIS MOBILE - Syafei Karim; Yulianto; Muhammad Ari Pratama (Universitas Islam Balitar, 2020)
Citra Niaga Samarinda Market is a very strategic place for traders selling in Citra Niaga Samarinda. Each market has a market levy which is managed by UPT Citra Niaga Samarinda under the auspices of the Samarinda City Trade Office. The purpose of the authors to conduct this research is to help the collection officers or market retribution officers who are in the image area of the Samarinda trade. Market levy collection clerk does not use records in doing billing every day. The results of this study are not to create difficulties in collecting market levies and making market reports by not using them manually. With the Mobile-based Information System for Pasar Citra Niaga Samarinda Market Retribution, it is very helpful in collecting market levies and does not commit fraud.